Conceptual Analysis of Vicharchika W.S.R. to Eczema: An Overview - Sahu, Narayan; Mohanta, Sarita; Panda, P K; Nayak, Utkalini; Panda, Sushmirekha (International Research Journal of Ayurveda & Yoga, 2023)
Introduction: In the Ayurvedic texts, all the skin disorders are included under the Kushtaroga. Which is further classified into two divisions, that is, Mahakushta and Kshudrakushta, Vicharchika is one among them. Vicharchika is stated as a Kshudra-Kushtha and Sadhya Kushtha by all acharya, but Kushtha is one among Ashta Mahagada. ence, it is difficult to cure. Vicharchika can be seen at any age but frequently seen in young age due to exposure to occupational, environmental factors, and mental stress. Junk food, irregular eating, repressing natural desires, using cosmetics and other chemicals, a polluted environment, a demanding existence, and emotional disorders all unquestionably play a significant role in the emergence of Vicharchika nowadays. Materials and Methods: From the Brihattrayi and its commentaries, the Laghutrayi, and other Ayurvedic texts, information regarding the Vicharchika (Eczema) was obtained. Results: According to all Acharyas, kustha is tridoshaja and Rakta pradoshaja vikara. In all kustharoga, the vitiation of Rakta and pitta is mentioned; hence, it is called Raktapradoshaja vikara. Vicharchika is one of the chronic skin diseases that have been mentioned in all Ayurvedic texts under Kshudra kustha. Conclusion: In the contemporary view of Vicharchika, it can be included as eczema. Long period of treatment in the form of suppressive and symptomatic (topical and systemic) is necessary in both therapies. In Ayurved kustha and Kshudra Kustha are broad concepts with pointed principle of management.